2018
DOI: 10.18632/oncotarget.24391
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-free treatment for patients with chronic hepatitis C and autoimmune liver disease: higher SVR rates with special precautions for deterioration of autoimmune hepatitis

Abstract: BackgroundInterferon-free treatment can achieve higher sustained virological response (SVR) rates, even in patients in whom hepatitis C virus (HCV) could not be eradicated in the interferon treatment era. Immune restoration in the liver is occasionally associated with HCV infection. We examined the safety and effects of interferon-free regimens on HCV patients with autoimmune liver diseases.ResultsAll 7 HCV patients with autoimmune hepatitis (AIH) completed treatment and achieved SVR. Three patients took predn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…There is a case series study of DAA-based therapy for 12 patients with chronic hepatitis C complicated with autoimmune liver disease[46]. One cirrhotic patient with autoimmune hepatitis developed serum ALT elevation and was obliged to receive prednisolone during the therapy with SOF/LDV.…”
Section: Discussionmentioning
confidence: 99%
“…There is a case series study of DAA-based therapy for 12 patients with chronic hepatitis C complicated with autoimmune liver disease[46]. One cirrhotic patient with autoimmune hepatitis developed serum ALT elevation and was obliged to receive prednisolone during the therapy with SOF/LDV.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this treatment is recommended in naïve patients or patients previously treated with interferon regimens, without cirrhosis or with compensated cirrhosis (Child A) and for 1 and 4 viral genotypes [ 26 ]. According to the C-EDGE TN and C-EDGE TE studies, another recommendation is established, since differences were observed in the sustained virologic response (SVR) rate based on the patient’s baseline viremia, it being adequate when it was less than 800,000 IU/mL [ 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, some evidence suggests alterations of immune status are DAA induced. Kanda et al treated 5 patients with HCV plus primary biliary cholangitis and 7 patients with HCV‐AIH overlap syndrome and achieved a 100% rate of SVR. Of the 7 patients with HCV‐AIH overlap syndrome, 3 received prednisone at baseline and 3 did not receive prednisone during DAA therapy; in 1 female patient with HCV‐AIH overlap syndrome plus cirrhosis who was treated with LDV/SOF, prednisone was not administered at baseline but was given after 8 weeks of liver chemistry abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of antiviral therapy of HCV, while highlighting the safety and effectiveness of DAA regimens, have also reported sporadic episodes of adverse effects associated with immune dysregulation. (2) We report the case of a woman with chronic hepatitis C and idiopathic thrombocytopenic purpura (ITP) who developed AIH during antiviral therapy with LDV/SOF.…”
Section: Autoimmune Hepatitis During Ledipasvir/sofosbuvir Treatment mentioning
confidence: 99%
See 1 more Smart Citation